Faktor Kesuksesan Sistem E-Office Rumah Sakit dalam Upaya Meningkatkan Kepuasan Pengguna - Ari Cahaya Puspitaningrum (Maranatha University Press, 2020)
Nowadays, hospital industries are aware of the importance of technological innovation that needs to be managed properly to drive business continuity and success in the future. The development of technological innovation in hospital industries has increased over time. This happens because of the desire to compete with each other continuously by utilizing technological innovation. This study has observed the existing information systems in the hospital, where the business process of the information system focuses on the hospital's internal correspondence process. This information system is called an e-office which is intended for the National Center General Hospital (RSUPN) Dr. Cipto Mangunkusumo. This study aims to determine what factors influence the successful implementation of the e-office system as seen from the evaluation of user satisfaction. Besides that, this study observed what efforts were made by the PT. Vidya Sentra Utama (Sevima) to create a successful and usable e-office system, where e-office is a large and complex system that includes more than 77 divisions with different business processes. Data collection methods used were interviews, observation, and document analysis. This study contributes to Sevima's knowledge of what factors of success need to be measured to determine user satisfaction and what needs to be done by Sevima's agile team to developing information systems and provide references for further research to evaluate an information system.